Moon (or Eid) Crescent Sign of the Femoral Head - Alshryda, Sattar (Cureus, 2020)
Avascular necrosis (AVN) of the femoral head following slipped capital femoral epiphysis (SCFE) is a serious complication that often leads to a permanent disability. Radiological findings of AVN may take up to two years to become apparent. This means painful waiting for children, parents, and treating teams. We would like to describe a new radiological sign that we noted in four patients. The sign has been named as the crescent moon sign or eid crescent sign. It may become visible as early as six weeks following surgery, and it carries a good prognosis that the femoral head is viable and will not develop AVN. Two out of the four patients were treated in our hospital by Ganz surgical dislocation. The other two patients had been featured in other publications, but the significance of the moon crescent signs, which were present, was not recognized or appreciated. All four patients did not develop AVN. A relatively similar radiological sign has been described in talus bone fractures (Hawkins' sign). Like SCFE, talus bone fractures have a high AVN rate. Both, the crescent moon sign and Hawkins' sign carry a good prognosis and indicate that the bone blood supply is restored.